2005
DOI: 10.1016/j.febslet.2005.06.013
|View full text |Cite
|
Sign up to set email alerts
|

PACAP protects neuronal differentiated PC12 cells against the neurotoxicity induced by a mitochondrial complex I inhibitor, rotenone

Abstract: In vivo and in vitro studies have suggested a neuroprotective role for Pituitary adenylate cyclase activating polypeptide (PACAP) against neuronal insults. Here, we showed that PACAP27 protects against neurotoxicity induced by rotenone, a mitochondrial complex I inhibitor that has been implicated in the pathogenesis of ParkinsonÕs disease (PD). The neuroprotective effect of PACAP27 was dose-dependent and blocked by its specific receptor antagonist, PACAP6-27. The effects of PA-CAP27 on rotenone-induced cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…Current therapies for Parkinson's disease mostly provide symptomatic relief but do not slow disease progression. Although pituitary adenylate cyclase-activating polypeptide and angiotensin II have been reported to protect against rotenone toxicity (Grammatopoulos et al, 2005;Wang et al, 2005a), the effect of growth factors in the rotenone model of Parkinson's disease had not been examined until our study. Here we demonstrate that bFGF, EGF, and GDNF promote survival of SH-SY5Y cells treated with rotenone, with bFGF offering the greatest level of protection.…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies for Parkinson's disease mostly provide symptomatic relief but do not slow disease progression. Although pituitary adenylate cyclase-activating polypeptide and angiotensin II have been reported to protect against rotenone toxicity (Grammatopoulos et al, 2005;Wang et al, 2005a), the effect of growth factors in the rotenone model of Parkinson's disease had not been examined until our study. Here we demonstrate that bFGF, EGF, and GDNF promote survival of SH-SY5Y cells treated with rotenone, with bFGF offering the greatest level of protection.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the extracellular ERK MAPK cascade is required for initiating the effect of PACAP on PC12 cell differentiation into sympathetic-like neurons (Vaudry et al, 2002e;Traverse et al, 1992;Frödin et al, 1994;Barrie et al, 1997;Tanaka et al, 1997a). In addition, PACAP prevents apoptosis of PC12 cells provoked by serum depletion, glutamate, prion protein fragment 106 -126, amyloid, or rotenone, through stimulation of the PKA pathway and subsequent activation of the MAPK cascade (Tanaka et al, 1997a;Onoue et al, 2002a,b,c;Wang et al, 2005). PACAP also prevents ceramide-induced apoptosis of PC12 cells by affecting signaling events downstream of the JNK (Hartfield et al, 1998).…”
Section: Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…Rotenone, another complex I inhibitor, inhibits the transfer of electrons from Fe-S centers to ubiquinone and thus reduces cellular ATP synthesis (Sherer et al, 2003;Hirata and Nagatsu, 2005). Both rotenone and MPP + mediate a variety of neuronal dysfunction and oxidative stress, leading to cell death (Cassarino et al 1999;Watabe et al 2004;Wang et al 2005). …”
Section: Introductionmentioning
confidence: 99%